10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BackgroundViolations in healthcare practice represent significant ethical and clinical challenges. Although often categorized as technical failures, they are strongly influenced by organizational culture and professional decision-making. Understanding how frontline practitioners conceptualize these deviations is essential for strengthening patient safety and ethical practice.ObjectiveTo explore the meanings attributed by healthcare professionals to violations in clinical practice.MethodsThis qualitative study employed online focus groups with 26 healthcare professionals from different disciplines, predominantly from the nursing workforce (73%). Data were collected using a structured discussion script, transcribed verbatim and analysed through Bardin's thematic content analysis. The study followed the COREQ guidelines to ensure methodological rigor. Ethical approval was obtained (Protocol 5.871.911).Ethical considerationsThe study was approved by the relevant Research Ethics Committee (Protocol No. 5.871.911). All participants received information about the study and provided informed consent before data collection. Participation was voluntary, and confidentiality and anonymity were protected throughout data collection, analysis and reporting.ResultsParticipants described violations as conscious deviations from safe practice and acknowledged their potential consequences for patient safety. The findings reveal a process of normalization of deviance driven by precarious working conditions, institutional traditions, and resource constraints. Although participants' perceptions converged with theoretical definitions regarding the operational characteristics of violations, their formal conceptual understanding remained limited. A tension also emerged between learning-oriented strategies and persistent punitive approaches focused on individual culpability.ConclusionHealthcare professionals recognize key elements of violations and emphasize the role of continuing education in addressing them. However, conceptual gaps and punitive cultures hinder the full appropriation of the construct in clinical practice. These findings contribute to nursing ethics by highlighting how organizational conditions shape the ethical management of deviations from safe practice.